2020
DOI: 10.1161/jaha.120.018136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anacetrapib on Cholesterol Efflux Capacity: A Substudy of the DEFINE Trial

Abstract: Background Anacetrapib is the only cholesteryl ester transfer protein inhibitor proven to reduce coronary heart disease (CHD). However, its effects on reverse cholesterol transport have not been fully elucidated. Macrophage cholesterol efflux (CEC), the initial step of reverse cholesterol transport, is inversely associated with CHD and may be affected by sex as well as haptoglobin copy number variants among patients with diabetes mellitus. We investigated the effect of anacetrapib on CEC and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…We have also found that genetically lower CETP was associated with higher levels of cholesterol efflux. This observation is concordant with previous reports of increased cholesterol efflux in patients treated with dalcetrapib and anacetrapib 28,29 . Genetically lower CETP was also associated with lower rates of cardiovascular outcomes, with 2.5% fewer CAD events per s.d.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have also found that genetically lower CETP was associated with higher levels of cholesterol efflux. This observation is concordant with previous reports of increased cholesterol efflux in patients treated with dalcetrapib and anacetrapib 28,29 . Genetically lower CETP was also associated with lower rates of cardiovascular outcomes, with 2.5% fewer CAD events per s.d.…”
Section: Discussionsupporting
confidence: 93%
“…Women with CETP lowering genetic variants had lower LDL-c and apoB levels and higher HDL-c, apoA and cholesterol efflux. In a substudy of the DEFINE trial, anacetrapib increased cholesterol efflux in men, but not women 29 . In that study, cholesterol efflux capacity was measured using fluorescently labeled cholesterol which mostly captures efflux through the ABCA1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The rs158477 locus could be a key player for these functions, and dalcetrapib may be mimicking its impact, hence explaining the pharmacogenomics association. Furthermore, in the light of our results, some of these effects could differ between men and women ( Metzinger et al, 2020 ), which may need to be taken into consideration in the future precision medicine interventions potentially implemented for dalcetrapib.…”
Section: Discussionmentioning
confidence: 92%
“…Anacetrapib treatment had an acceptable side effect profile, did not result in the adverse CV effects seen with torcetrapib, and reduced atherosclerotic CVD [ 120 ], which are reasons for using the drug in future studies re-evaluating the hypothesis that CETP inhibition is cardioprotective. Notably, in a post-hoc substudy of DEFINE including about 600 patients, anacetrapib’s ability to modulate CEC was evaluated [ 121 ]. This study provided evidence of a promoting effect of the drug on this HDL function, which is not affected by the diabetes status, but it was blunted in T2DM subjects with allele “2” of haptoglobin, a protein associated with HDL whose polymorphism has been associated with impaired HDL functions [ 122 ] and increased CV risk in T2DM patients [ 123 ].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%